The Impact of Experimental Research-Based Learning Modules on Students' Affective Domain: A Study on Religious Moderation in Chemistry Education - Adean Mayasri; Muhammad Reza; M. Rizki Asyifa; Kania Ulayya (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2024)
Islamic Religious Colleges (PTKI) 's key mission is to promote religious moderation for students. This aspect is currently missing in the Chemical Education Studies Program curriculum. To address this, we constructed a teaching module that applied the 4S-TMD method (Selection, structuring, characterization, and didactical reduction). This work is based on experimental data of using waste palm coconut shells as activated carbon for methylene blue dye adsorption, which formed two modules: Inorganic Chemistry II (Module A) and Instrumental Analysis Chemistry (Module B). The selection phase was designed with graduate learning outcomes (GLO), learning content, and indicators of religious moderation in module design. The item content validity index (I-CVI), measuring content validity, reached an excellent average of 0.98. During the structuring phase, laboratory experimental results were mapped conceptually. Module A performed excellently, with a validity of 85%, whereas Module B was below 80%. After the refinement steps, both modules reached 100% validity. The measure of the value of religious moderation of GLO indicates >60% for 10 variables, whereas the self-assessment of the nine values of religious moderation of students shows very good (above 20%). This is the first study applying religious moderation to chemistry education and showed that the 4S-TMD method of implementing the 4S-TS method was effective (4.9/5.0 for eligibility). Sow enjoyably integrates chemistry and science education with similar values, which can take place using their type.